Implementation of carrageenan and xanthan gum in "raja" banana (Musa sapientum) for coating application. Issue 1 (July 2021) - Al-Baarri, A N; Widayat,; Legowo, A M; Apsari, N P I; Perdanawati, D; Negara, K R; Pangestika, W; Lestari, F P; Mawarid, A A
Abstract: "Raja" banana ( Musa sapientum ) is a type of banana that is often consumed in Indonesia. Raja bananas provides several benefits due to nutrients content, such as bioactive phenolics, antioxidants, potassium, vitamin C and also high carbohydrate content that changes color and texture during ripening. Preservation method was used to suppress this physical changes. This research was done to analyze color in "Raja" bananas and its shelf life after the treatment using iota carrageenan and xanthan gum as coating material. The four formulas of coating were applied in banana by full surface coating in banana and stored in room temperature. The color change and texture of banana peel were observed for 5 days. As result, the best coating composition was iota carrageenan since the coating using this material provided moist appearance during ripening process, indicating the inhibition in banana's ripening. As conclusion, iota carrageenan may be applied as coating material in "Raja" banana that enable to suppress the physical changes on color and texture during ripening.